2018
DOI: 10.1016/j.wjorl.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antibiotics on smell dysfunction

Abstract: ObjectiveViral or bacterial respiratory infections can cause long-lasting olfactory dysfunction. Antibiotic therapy is indicated in severe cases; however, it is unclear whether antibiotic use produces a positive, negative, or null effect on olfactory function. This retrospective study sought to determine whether antibiotic use has an influence on odor identification and detection threshold test scores of patients with smell dysfunction secondary to upper respiratory infections (URIs), lower respiratory infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Doxycycline reduces bacterial colonization and therefore decreases the inflammation of sino-nasal mucosa. 20 We believe that combination of the above-mentioned properties improved hyposmia in our participants. However, more investigations are needed to define the exact involved mechanism.…”
Section: Discussionmentioning
confidence: 66%
“…Doxycycline reduces bacterial colonization and therefore decreases the inflammation of sino-nasal mucosa. 20 We believe that combination of the above-mentioned properties improved hyposmia in our participants. However, more investigations are needed to define the exact involved mechanism.…”
Section: Discussionmentioning
confidence: 66%
“…Viral or bacterial upper respiratory infections can result in OD, and in severe cases, antibiotic therapy is indicated which complicates the relation to ORAE. In an analysis of bactericidal antibiotic use on OD in patients with an upper respiratory etiology, studies found lower detection thresholds in patients who had not taken antibiotics 20 . Moreover, thresholds were lower for bactericidal antibiotic users than for bacteriostatic users.…”
Section: Discussionmentioning
confidence: 98%
“…In an analysis of bactericidal antibiotic use on OD in patients with an upper respiratory etiology, studies found lower detection thresholds in patients who had not taken antibiotics. 20 [3.01, 3.18]) were noted to have significant signals for hyposmia and parosmia. It has been well-established that the olfactory sensory neural pathway includes numerous brain regions implicated in the pathophysiology of several neuropsychiatric disorders, such as depression, schizophrenia, autism spectrum disorder, obsessive-compulsive disorder, and attention-deficit/hyperactivity disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the neuroepithelium at the interface of the environment places its cells at risk from damage from viruses [74], bacteria [93], nanoparticles [94], and other airborne xenobiotics [95]. Such damage is well established [96], with some viruses being capable of penetrating the brain from this region [74] (Box 3).…”
Section: Damage To the Olfactory Neuroepitheliummentioning
confidence: 99%